Development of a novel LAMP diagnostic method for visible detection of swine Pasteurella multocida - Dongbo Sun; Jianfa Wang; Rui Wu; Chunren Wang; Xianjing He; Jiasan Zheng; Huanmin Yang (Veterinary Research Communications, 2010)

Development of Juglans Regia SSR Markers by Data Mining of the EST Database - Rui Zhang; AnDan Zhu; XinJian Wang; Jun Yu; HongRong Zhang; JiangSheng Gao; YunJiang Cheng; XiuXin Deng (Plant Molecular Biology Reporter, 2010)

Extraction of essential oils from garlic (Allium sativum) using ligarine as solvent and its immunity activity in gastric cancer rat - Rui Li; Wei-chang Chen; Wei-peng Wang; Wen-yan Tian; Xue-guang Zhang (Medicinal Chemistry Research, 2010)

Analysis of the essential oil of magnolia and its effect on antioxidant enzyme activity, sCD40L and phosphorylate-activate Akt protein levels in gastric cancer mice - Rui Li; Wei-chang Chen; Wei-peng Wang; Wen-yan Tian; Xue-guang Zhang (Medicinal Chemistry Research, 2010)

Synthesis and biological evaluation of cyclopenten-1-one Mannich base oxovanadium compound - Juan Tian; Dongliu Li; Fengying Zhai; Xiaohong Wang; Rui Li (Medicinal Chemistry Research, 2010)

The pentapeptide PLNPK inhibits systemic lupus erythematosus-associated renal damage - Jun-qiang Lv; Wen Zhang; Song Wang; Lin Zhao; Rui Ma; Jin-wei Hu; Li-juan Wang; Jie Meng; Chun-lei Zhou; Gang Lin; Rong Lu; Zhi Yao (Inflammation Research, 2010)

The effect of the expression of angiotensin II on extracellular matrix metalloproteinase inducer (EMMPRIN) in macrophages is mediated via the AT1/COX-2/PGE2 pathway - Li-xia Yang; Jin-shan Ye; Rui-wei Guo; Hong Liu; Xian-mei Wang; Feng Qi; Chuanming Guo (Inflammation Research, 2010)

Multiple induced mutagenesis for improvement of ethanol production by Kluyveromyces marxianus - Zong-wen Pang; Jing-juan Liang; Xiao-juan Qin; Ji-rui Wang; Jia-xun Feng; Ri-bo Huang (Biotechnology Letters, 2010)

Molecular phylogeny of Ranunculaceae based on rbc L sequences - Ying-fan Cai; Sheng-wei Li; Min Chen; Ming-feng Jiang; Yi Liu; Yong-fang Xie; Quan Sun; Huai-zhong Jiang; Neng-wen Yin; Ling Wang; Rui Zhang; Cheng-lin Huang; et al. (Biologia, 2010)

Preliminary study on the freeze-drying of human bone marrow-derived mesenchymal stem cells - Shao-zhi Zhang; Huan Qian; Zhen Wang; Ju-li Fan; Qian Zhou; Guang-ming Chen; Rui Li; Shan Fu; Jie Sun (Journal of Zhejiang University-SCIENCE B, 2010)

Cytotoxic Activity and DNA-binding Properties of Xanthone Derivatives - Rui Shen; Peng Wang; Ning Tang (Journal of Fluorescence, 2010)

Genome-wide identification and evaluation of novel internal control genes for Q-PCR based transcript normalization in wheat - Xiang-Yu Long; Ji-Rui Wang; Thérèse Ouellet; Hélène Rocheleau; Yu-Ming Wei; Zhi-En Pu; Qian-Tao Jiang; Xiu-Jing Lan; You-Liang Zheng (Plant Molecular Biology, 2010)

Regulation of β cleavage of amyloid precursor protein - Jun-Feng Wang; Rui Lu; Yi-Zheng Wang (Neuroscience Bulletin, 2010)

The functional expression of calcium-sensing receptors in BRL cells and related signal transduction pathway responsible for intracellular calcium elevation - Wenjing Xing; Guangwei Li; Yuhui Xi; Jin Guo; Hongzhu Li; Hongxia Li; Weihua Zhang; Li Zhang; Lingyun Wu; Rui Wang; Changqing Xu (Molecular and Cellular Biochemistry, 2010)

Temporal and spatial characteristics of the urban heat island during rapid urbanization in Shanghai, China - Kaixuan Zhang; Rui Wang; Chenchen Shen; Liangjun Da (Environmental Monitoring and Assessment, 2010)

Spatio-Temporal Variability of Soil Respiration of Forest Ecosystems in China: Influencing Factors and Evaluation Model - Ze-Mei Zheng; Gui-Rui Yu; Xiao-Min Sun; Sheng-Gong Li; Yue-Si Wang; Ying-Hong Wang; Yu-Ling Fu; Qiu-Feng Wang (Environmental Management, 2010)

Identification of the VP92R gene from infectious spleen and kidney necrosis virus - Xiaopeng Xu; Qingxia Lu; Rui Wang; Ting Lin; Shaoping Weng; Ling Lu; Zhongsheng Li; Xiaoqiang Yu; Junliang Tang; Jianguo He (Virus Genes, 2010)

Responses of Mikania micrantha, an Invasive Weed to Elevated CO2: Induction of β-Caryophyllene Synthase, Changes in Emission Capability and Allelopathic Potential of β-Caryophyllene - Rui-Long Wang; Christian Staehelin; Shao-Lin Peng; Wen-Tian Wang; Xi-Mei Xie; Hui-Ning Lu (Journal of Chemical Ecology, 2010)

Identification, localization, and characterization of putative USP genes in barley - Wei-Tao Li; Yu-Ming Wei; Ji-Rui Wang; Chun-Ji Liu; Xiu-Jin Lan; Qian-Tao Jiang; Zhi-En Pu; You-Liang Zheng (Theoretical and Applied Genetics, 2010)

The functional expression of calcium-sensing receptor in the differentiated THP-1 cells - Yu-hui Xi; Hong-zhu Li; Wei-hua Zhang; Li-na Wang; Li Zhang; Yan Lin; Shu-zhi Bai; Hong-xia Li; Ling-yun Wu; Rui Wang; Chang-qing Xu (Molecular and Cellular Biochemistry, 2010)

Isolation and characterization of a gene encoding a polyethylene glycol-induced cysteine protease in common wheat - Qing-Wei Zang; Cai-Xiang Wang; Xu-Yan Li; Zhi-Ai Guo; Rui-Lian Jing; Jun Zhao; Xiao-Ping Chang (Journal of Biosciences, 2010)

Isolation and characterization of microsatellite markers from Lagerstroemia caudata (Lythraceae) and cross-amplification in other related species - Ming Cai; Rui Meng; Hui-Tang Pan; Yi-Ke Gao; Ming Sun; Ping Song; Xue-Feng Wang; Qi-Xiang Zhang (Conservation Genetics Resources, 2010)

Seasonal variation analysis of atmospheric CH4, N2O and CO2 in Tianjin offshore area - ShaoFei Kong; Bing Lu; Bin Han; ZhiPeng Bai; Zhun Xu; Yan You; LiangMao Jin; XiaoYang Guo; Rui Wang (Science China Earth Sciences, 2010)

Testicular toxicity induced by dietary cadmium in cocks and ameliorative effect by selenium - Jin-Long Li; Rui Gao; Shu Li; Jin-Tao Wang; Zhao-Xin Tang; Shi-Wen Xu (BioMetals, 2010)

MicroRNA-17 post-transcriptionally regulates polycystic kidney disease-2 gene and promotes cell proliferation - Huan Sun; Qing-Wei Li; Xiao-Yan Lv; Jian-Zhong Ai; Qiu-Tan Yang; Jing-Jing Duan; Guo-Hui Bian; Yan Xiao; Yi-Dong Wang; Zheng Zhang; Yu-Hang Liu; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

Radiosonde observations of high-latitude planetary waves in the lower atmosphere - Rui Wang; ShaoDong Zhang; Fan Yi (Science China Earth Sciences, 2010)

Neural circuits and temporal plasticity in hindlimb representation of rat primary somatosensory cortex: revisited by multi-electrode array on brain slices - Dan-Dan Wang; Zhen Li; Ying Chang; Rui-Rui Wang; Xue-Feng Chen; Zhen-Yu Zhao; Fa-Le Cao; Jian-Hui Jin; Ming-Gang Liu; Jun Chen (Neuroscience Bulletin, 2010)

Sequence and expression analysis of the gene encoding inducible cAMP early repressor in tilapia - Ming Chen; Rui Wang; Xi Gan; Aiying Lei; Chao Li; Xiaoli Yu; Jun Huang; Ting Huang; Wanwen Liang (Molecular Biology Reports, 2010)

Down-regulation of Pkd2 by siRNAs suppresses cell–cell adhesion in the mouse melanoma cells - Guo-Hui Bian; Ge Cao; Xiao-Yan Lv; Qing-Wei Li; Huan Sun; Yan Xiao; Jian-Zhong Ai; Qui-Tan Yang; Jing-Jing Duan; Yi-Dong Wang; Zheng Zhang; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

Mechanism of action of two insect toxins huwentoxin-III and hainantoxin-VI on voltage-gated sodium channels - Rui-lan Wang; Su Yi; Song-ping Liang (Journal of Zhejiang University-SCIENCE B, 2010)

Rain follows logging in the Amazon? Results from CAM3–CLM3 - Rui Mei; Guiling Wang (Climate Dynamics, 2010)

Bacteria isolated from dripping water in the oligotrophic Heshang cave in Central China - Qianying Liu; Hongmei Wang; Rui Zhao; Xuan Qiu; Linfeng Gong (Journal of Earth Science, 2010)

Inhibition of Fusarium graminearum growth and deoxynivalenol production by geocarpospheric bacterial strains - Cuijuan Shi; Peisheng Yan; Kai Wang; Rui Chen (Journal of Earth Science, 2010)

Degradation of Polycyclic Aromatic Hydrocarbons by Crude Extracts from Spent Mushroom Substrate and its Possible Mechanisms - Xuanzhen Li; Xiangui Lin; Jing Zhang; Yucheng Wu; Rui Yin; Youzhi Feng; Yong Wang (Current Microbiology, 2010)

Diffusive coevolution and mutualism maintenance mechanisms in a fig–fig wasp system - Rui-Wu Wang; Bao-Fa Sun; Qi Zheng (Ecology, 2010)
In reciprocal mutualism systems, the exploitation events by exploiters might disrupt the reciprocal mutualism, wherein one exploiter species might even exclude other coexisting exploiter species over an evolutionary time frame. What remains unclear is how such a community is maintained. Niche partitioning, or spatial heterogeneity among the mutualists and exploiters, is generally believed to enable stability within a mutualistic system. However, our examination of a reciprocal mutualism between a fig species ( Ficus racemosa ) and its pollinator wasp ( Ceratosolen fusciceps ) shows that spatial niche partitioning does not sufficiently prevent exploiters from overexploiting the common resource (i.e., the female flowers), because of the considerable niche overlap between the mutualists and exploiters. In response to an exploiter, our experiment shows that the fig can (1) abort syconia‐containing flowers that have been galled by the exploiter, Apocryptophagus testacea , which oviposits before the pollinators do; and (2) retain syconia‐containing flowers galled by Apocryptophagus mayri , which oviposit later than pollinators. However, as a result of (2), there is decreased development of adult non‐pollinators or pollinator species in syconia that have not been sufficiently pollinated, but not aborted. Such discriminative abortion of figs or reduction in offspring development of exploiters while rewarding cooperative individuals with higher offspring development by the fig will increase the fitness of cooperative pollinating wasps, but decrease the fitness of exploiters. The fig–fig wasp interactions are diffusively coevolved, a case in which fig wasps diversify their genotype, phenotype, or behavior as a result of competition between wasps, while figs diverge their strategies to facilitate the evolution of cooperative fig waps or lessen the detrimental behavior by associated fig wasps. In habitats or syconia that suffer overexploitation, discriminative abortion of figs or reduction in the offspring development of exploiters in syconia that are not or not sufficiently pollinated will decrease exploiter fitness and perhaps even drive the population of exploiters to local extinction, enabling the evolution and maintenance of cooperative pollinators through the movement between habitats or syconia (i.e., the metapopulations).

UNC-64 and RIC-4, the plasma membrane-associated SNAREs syntaxin and SNAP-25, regulate fat storage in nematode Caenorhabditis elegans - Qiu-Li Wu; Qi Rui; Ke-Wen He; Lu-Lu Shen; Da-Yong Wang (Neuroscience Bulletin, 2010)

Research development of the pathogenesis pathways for neuroschistosomiasis - Peng Wang; Ming-Can Wu; Shi-Jie Chen; Guo-Cai Luo; Xiang-Ling Cheng; Zhan-Sheng Zhu; Guang-Rui Zhao (Neuroscience Bulletin, 2010)

Expression and characterization of Momordica Chanrantia anti-hyperglycaemic peptide in Escherichia coli - Si-Xiu Liu; Zhong-Ping Fu; Rui-Min Mu; Zhi-Bi Hu; Fu-Jun Wang; Xiang-Rong Wang (Molecular Biology Reports, 2010)

Cross-protection against influenza virus infection by intranasal administration of M2-based vaccine with chitosan as an adjuvant - Zhiwei Sui; Quanjiao Chen; Rui Wu; Hongbo Zhang; Mei Zheng; Hanzhong Wang; Ze Chen (Archives of Virology, 2010)

A PKC-β inhibitor protects against cardiac microvascular ischemia reperfusion injury in diabetic rats - Liping Wei; Dongdong Sun; Zhiyong Yin; Yuan Yuan; Andrew Hwang; Yingmei Zhang; Rui Si; Rongqing Zhang; Wenyi Guo; Feng Cao; Haichang Wang (Apoptosis, 2010)

Trend and change-point analyses of streamflow and sediment discharge in the Yellow River during 1950–2005 - Peng Gao; Xunchang Zhang; Xinming Mu; Fei Wang; Rui Li; Xiaoping Zhang (Hydrological Sciences Journal, 2010)

Molecular diversity and phylogenetic analyses of y-type high-molecular-weight glutenin promoters from different genomes in Triticeae - Qian-Tao Jiang; Yu-Ming Wei; Ji-Rui Wang; Ze-Hong Yan; You-Liang Zheng (Plant Systematics and Evolution, 2010)

Long-term effect of re-vegetation on the microbial community of a severely eroded soil in sub-tropical China - Huan Deng; Bin Zhang; Rui Yin; Hui-li Wang; Susan M. Mitchell; Bryan S. Griffiths; Timothy John Daniell (Plant and Soil, 2010)

Activation of TRPA1 channels by fenamate nonsteroidal anti-inflammatory drugs - Hongzhen Hu; Jinbin Tian; Yingmin Zhu; Chunbo Wang; Rui Xiao; Jeffrey M. Herz; Jackie D. Wood; Michael X. Zhu (Pflügers Archiv - European Journal of Physiology, 2010)

Photocatalytic degradation of organic dyes by Er3+:YAlO3/TiO2 composite under solar light - Jun Wang; Yingpeng Xie; Zhaohong Zhang; Jia Li; Chengwu Li; Liquan Zhang; Zhiqiang Xing; Rui Xu; Xiangdong Zhang (Environmental Chemistry Letters, 2010)

Microbial community structure and diversity in a native forest wood-decomposed hollow-stump ecosystem - Bao-Yu Tian; Qin-Geng Huang; Yan Xu; Chun-Xiang Wang; Rui-Rui Lv; Jian-Zhong Huang (World Journal of Microbiology and Biotechnology, 2010)

Effects of organic matter incorporation on nitrous oxide emissions from rice-wheat rotation ecosystems in China - Zhisheng Yao; Zaixing Zhou; Xunhua Zheng; Baohua Xie; Baoling Mei; Rui Wang; Klaus Butterbach-Bahl; Jianguo Zhu (Plant and Soil, 2010)

Genetic transformation of the bast fiber plant ramie (Boehmeria nivea Gaud.) via Agrobacterium tumefaciens - Xiongfeng Ma; Chunming Yu; Shouwei Tang; Sandui Guo; Rui Zhang; Yanzhou Wang; Aiguo Zhu; Siyuan Zhu; Heping Xiong (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Scutellarin exerts its anti-hypertrophic effects via suppressing the Ca2+-mediated calcineurin and CaMKII signaling pathways - Zhen-Wei Pan; Ying Zhang; Dong-Hua Mei; Rui Zhang; Jing-Hao Wang; Xiang-Ying Zhang; Chang-Qing Xu; Yan-Jie Lu; Bao-Feng Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Identification of low abundance polyA-binding proteins in Arabidopsis chloroplast using polyA-affinity column - Rui-Juan Ni; Zhuo Shen; Chuan-Ping Yang; Ya-Dan Wu; Ying-Dong Bi; Bai-Chen Wang (Molecular Biology Reports, 2010)

Inhibitor of DNA binding-1 promotes the migration and proliferation of endothelial progenitor cells in vitro - Hong Wang; Yang Yu; Rui-wei Guo; Yan-kun Shi; Ming-bao Song; Jian-fei Chen; Shi-yong Yu; Yang-guang Yin; Pan Gao; Lan Huang (Molecular and Cellular Biochemistry, 2010)

Analysis of the composition and concentration of fatty acids in transgenic soybean (cp4-epsps1) oil - Yukui Rui; Wenya Wang; Lei Chen (Journal of Consumer Protection and Food Safety, 2010)

Bacterial communities in PAH contaminated soils at an electronic-waste processing center in China - Wen Zhang; Hui Wang; Rui Zhang; Xie-Zhi Yu; Pei-Yuan Qian; M. H. Wong (Ecotoxicology, 2010)